Identification and characterisation of a novel small galectin in razor clam (Sinonovacula constricta) with multiple innate immune functions. (April 2019) - Bai, Yuqi; Niu, Donghong; Li, Yan; Bai, Yulin; Lan, Tianyi; Peng, Maoxiao; Dong, Zhiguo; Sun, Fanyue; Li, Jiale
Abstract: Galectins are lectins possessing an evolutionarily conserved carbohydrate recognition domain (CRD) with affinity for β-galactoside. The key role played by innate immunity in invertebrates has recently become apparent. Herein, a full-length galectin (ScGal) was identified in razor clam ( Sinonovacula constricta ). The 528 bp open reading frame encodes a polypeptide of 176 amino acids with a single CRD and no signal peptide. ScGal mRNA transcripts were mainly expressed in hemolymph and gill, and were significantly up-regulated following bacterial challenge. Recombinant rScGal protein binds to and aggregates various bacteria, and has affinity for peptidoglycan, lipoteichoic acid andd -galactose. The protein also stimulates hemocytes to phagocytose invading bacterial pathogens. ScGal is an important immune factor in innate immunity, and a small protein with multiple important functions. Highlights: A single CRD galectin was identified in razor clam ( Sinonovacula constricta ). ScGal mRNA is mainly expressed in hemolymph and gill. ScGal expression is up-regulated following bacterial challenge. ScGal aggregates bacteria, and binds PGN, LTA andd -galactose. ScGal also stimulates hemocytes to phagocytose invading bacterial pathogens.